MICROECONOMIC DETERMINANTS OF LOSSES IN FINANCIAL INSTITUTIONS DURING THE CRISIS - CEPPARULO , Alessandra; FORTE , Antonio (Journal of Advanced Studies in Finance, 2014)
This paper tries to find out the determinants of bank losses and their extent during the sub-prime crisis, analysing banks structure and performance. The results of the proposed probit models confirm the new tendencies of the international regulations inspired both by the Basel III Accord and the Financial Stability Board: sound patrimonial ratios together with safer assets structures are prerequisites for the “too big to fail” financial institutions and they favor a decrease in the probability of suffering losses.